2022
DOI: 10.1177/01455613221084076
|View full text |Cite
|
Sign up to set email alerts
|

Successful removal of metallic foreign body in the neck-mediastinum via the parapharyngeal space approach

Abstract: Neck-mediastinum foreign body (FB) is a common emergency in otorhinolaryngology head and neck surgery departments, and it can be lethal. We present a case of an uncommon foreign body in the neck-mediastinum. The FB was metallic and about 12 cm long. A 74-year-old male accidentally swallowed a metallic FB that lodged in his throat for > 3 days. The intake of the object was associated with smoking a peace pipe, and was an indication for surgery. Aerodermectasia was observed in the neck upon physical examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Thus, imaging technology plays an important role in identifying foreign bodies in the nasal cavity. A case report involving older adults found that CT imaging can accurately identify high-density foreign bodies in the mediastinum of the neck, whereas electronic laryngoscopy cannot detect foreign bodies in the larynx or pyriform sinus[ 8 ]. CT imaging also helps in distinguishing between rhinitis caused by small foreign bodies and those caused by non-foreign bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, imaging technology plays an important role in identifying foreign bodies in the nasal cavity. A case report involving older adults found that CT imaging can accurately identify high-density foreign bodies in the mediastinum of the neck, whereas electronic laryngoscopy cannot detect foreign bodies in the larynx or pyriform sinus[ 8 ]. CT imaging also helps in distinguishing between rhinitis caused by small foreign bodies and those caused by non-foreign bodies.…”
Section: Discussionmentioning
confidence: 99%